2008
DOI: 10.1542/peds.2008-0952
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Contact With Families After the Death of Pediatric Patients: A Survey of Pediatric Critical Care Practitioners' Beliefs and Self-Reported Practices

Abstract: A high proportion of pediatric critical care physicians have contacted bereaved families and attended funerals after the death of a child patient. These practices were consistently associated with the belief that such follow-up contact helps the family or the practitioner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 14 publications
0
41
2
Order By: Relevance
“…[33][34][35] Collaborative communication promotes open conversation about decision-making, allows for ongoing assessments of family need, and takes into account the family's knowledge about the child's illness. 3,13,[36][37][38] A metasummary of qualitative analyses of patient and family needs in pediatric palliative care found that family needs are quite high, specifically in the areas of interactions with staff, psychosocial needs, spiritual issues, decision-making, sibling needs, cultural needs, pain and symptom management, information needs, and health care delivery and accessibility. 39 More specifically, in a qualitative study of parents who had recently participated in difficult conversations with physicians in the pediatric intensive care setting, 11 specific physician interpersonal behaviors were identified as helpful to parents 40 : empathy, availability, treating the child as an individual, respecting parents' knowledge of the child, allowing hope, body contact that communicated warmth, thoroughness, going beyond the call of duty, accountability, willingness to be questioned, and attention to the suffering of the child.…”
Section: Improving Clinician-family Relationships and Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Collaborative communication promotes open conversation about decision-making, allows for ongoing assessments of family need, and takes into account the family's knowledge about the child's illness. 3,13,[36][37][38] A metasummary of qualitative analyses of patient and family needs in pediatric palliative care found that family needs are quite high, specifically in the areas of interactions with staff, psychosocial needs, spiritual issues, decision-making, sibling needs, cultural needs, pain and symptom management, information needs, and health care delivery and accessibility. 39 More specifically, in a qualitative study of parents who had recently participated in difficult conversations with physicians in the pediatric intensive care setting, 11 specific physician interpersonal behaviors were identified as helpful to parents 40 : empathy, availability, treating the child as an individual, respecting parents' knowledge of the child, allowing hope, body contact that communicated warmth, thoroughness, going beyond the call of duty, accountability, willingness to be questioned, and attention to the suffering of the child.…”
Section: Improving Clinician-family Relationships and Communicationmentioning
confidence: 99%
“…37 Borasino and colleagues have also reported that such contact may also help physicians process their own feelings, yet only a low percentage of physicians reported active means of contact with the family, such as writing, calling, or meeting with family members; more often, passive means were used, such as giving families contact information at the time of death or designating other staff to offer follow-up. 38 As previously stated, the pediatric palliative standard of care embraces bereavement support; however, parents' recollections and other research have offered evidence that adequate bereavement follow-up is not occurring. 56 Physicians explain that their lack of time, unawareness that family members experience this lack of closure as abandonment, and personal and emotional barriers keep them from following up with families.…”
Section: Providing Bereavement Carementioning
confidence: 99%
“…3 Families value contact with the staff after the death of a child, which may help families with the bereavement process. 11 Bereavement follow-up is part of comprehensive supportive care. Many families experience the loss not only of a child but also of the community they have shared with the interdisciplinary team.…”
Section: Introductionmentioning
confidence: 99%
“…Some parents have been receptive to staff attending funerals, and conversely, they were disappointed when staff did not attend. 11 Although there has been a strong movement to improve supportive care, the literature reveals gaps that exist between the family's needs and the adequacy of care provided by health care professionals. 12 Families benefit from staff members who are knowledgeable and sensitive to family dynamics during stressful situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation